Antigenic Proteins from the Excretory-Secretory Products of Toxocara canis Larvae and Evaluation of Their Potential for Immunodiagnostics of Larval Toxocarosis - Skulinová, Kateřina; Novák, Jan; Kolářová, Libuše; Kašný, Martin (Acta parasitologica, 2022)
BACKGROUND: Larval toxocarosis is a zoonosis caused by larvae of Toxocara canis and T. cati, a gastrointestinal nematode of canids and felids, respectively. Diagnosis is usually performed by ELISA IgG using Toxocara excretory-secretory products as an antigen. Due to laboriousness of isolation of the products and subsequent process of standardization of antigenic compounds, routine use of this method is limited and can produce inaccurate diagnostical results. The purpose of this study was to discover new specific antigenic proteins that could be used in routine serological methods of larval toxocarosis. MATERIALS AND METHODS: Toxocara excretory-secretory products were collected and separated by SDS-PAGE. Proteins from the gel were electro-transferred to a membrane and incubated with mouse sera. Antigenic proteins were analyzed using the liquid chromatography-tandem mass spectrometry approach. Selected proteins were prepared in recombinant form and tested with mice and human sera by ELISA and Western blot. RESULTS: A total of four recombinant protein antigens were prepared (rTc-TES-26, rTc-ASA, rTc-PDP, and rTc-ASP). They were analyzed by ELISA and Western blot using mice and human sera. For all sera, three of the four recombinant antigens correlated with Toxocara excretory-secretory products in ELISA analysis. By Western blot, the infection was confirmed in all experimentally infected mice and two out of seven human patients. CONCLUSION: Combination of the presented methods and analyses represents a possible method of effective identification of Toxocara protein antigens for the purpose of routine serodiagnosis.
Keywords: Diagnostics; myši; Animals; Larva; toxokaróza; Toxocarosis; Enzyme-Linked Immunosorbent Assay; Humans; Recombinant protein; Toxocariasis; Toxocara; Antigen; Antigens, Helminth; lidé; Toxocara canis; Mice; zvířata; ELISA; antigeny helmintové; larva